BUDAYA ORGANISASI DAN KOMPENSASI : PENGARUHNYA TERHADAP MOTIVASI DAN KINERJA KARYAWAN (Studi pada PT. Sang Hyang Seri Kantor Regional III Malang) - Ivan Adi Kurniawan; Misbahuddin Azzuhri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Employee’s performance of is a result from people in their job and something important for organizing or corporating. Many aspects could be affect employee’s performance such as corporate culture, compensation, and motivation. The aims of this research are to analyze the influence of corporate culture and compensation and on motivation, and its impact toward the employee’s performance at PT Sang Hyang Seri Branch Office III Malang. Corporate culture and compensation are independent variables, performance of employee is dependent variable, and motivation is intervening variable. The sample for this research is all employees at this corporation (50 persons). The method that used to analyze the research data is uses double linier regression analyst by the computer software program. The researcher has used validation test, reliability test, normality test, and path analysis. Base on this research, we will know about the direct and indirect influence of corporate organization and compensation to employee performance thought motivation. Keywords : Corporate Culture, Compensation, Motivation, Performance of Employee